Association of Cytochrome P4502C9, Vitamin K Epoxide Reductase and Gamma-Glutamyl Carboxylase Gene Polymorphisms with Warfarin Dose Requirement Among Sudanese Patients - Babiker, Rowida; Elzaki , Salah Eldin Gumaa; Elgoraish, Amanda G.; Osman, Hussam Ali (International Journal of Innovative Research in Medical Science, 2023)
Background: Warfarin is a common anticoagulant drug that has a narrow therapeutic index; a higher dose causes excessive bleeding and a lower dose leads to cerebrovascular clotting and stroke in patients. The management of warfarin therapy is challenging because there is variability in patient response due to many factors. Genetic factors that are most relevant, such as CYP2C9, and andVKOR, are the target site for warfarin. The study aimed to investigate the association between CYP2C9*2, VKORC1 (-1639 G>A), and GGCX T>G polymorphisms with warfarin daily dose in Sudanese patients on warfarin treatment referred to anti-coagulation clinics in Khartoum State, Sudan. Method: A cross-sectional descriptive study was conducted on randomly selected 107 patients on warfarin with different clinical indications. Their genotype was analyzed by Polymerase Chain Reaction (PCR) and Restriction Fragment Length Polymorphism (RFLP) to determine the polymorphisms. Result: The study revealed that CYP2C9 genotype wild type was more frequent than heterozygote. For VKORC1 the frequency of the A allele was 61.8% and for the G allele was 38.2%, the GGCX genotype was observed only in wild-type and homozygous genotypes (89.7%& 10.3%, respectively). The t allele of GGCX was higher than the G alleles. Conclusion: The most common polymorphisms that revealed high significance on warfarin dose determination were VKORC1A/giving evidence to new guidelines dose requirements according to the patient genotype. These new dose requirement recommendations may lead to a significant improvement in the management of anticoagulant therapy in Sudan.